2014
DOI: 10.1371/journal.pone.0104128
|View full text |Cite|
|
Sign up to set email alerts
|

Ocular Morbidity and Health Seeking Behaviour in Kwara State, Nigeria: Implications for Delivery of Eye Care Services

Abstract: BackgroundThere is currently limited information as to which conditions are most prevalent in communities in developing countries. This makes effective planning of eye services difficult.Methods3,899 eligible individuals were recruited and examined in a cross-sectional survey in Asa Local Government Area, Nigeria. Those who self-reported an ocular morbidity were also asked about their health-seeking behaviour. Health records of local facilities were reviewed to collect information on those presenting with ocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 15 publications
5
27
1
Order By: Relevance
“…Patients examined were from all age group with the maximum numbers in the age group 1 -10 years (18%), subsequently followed by 11 -20 years (16%), 41 -50 years (15.6%) ( Figure 3). These findings are similar to a study done in India and Nigeria that showed that children are affected with ocular morbidity conditions than the older age [12] [13].…”
Section: Discussionsupporting
confidence: 91%
“…Patients examined were from all age group with the maximum numbers in the age group 1 -10 years (18%), subsequently followed by 11 -20 years (16%), 41 -50 years (15.6%) ( Figure 3). These findings are similar to a study done in India and Nigeria that showed that children are affected with ocular morbidity conditions than the older age [12] [13].…”
Section: Discussionsupporting
confidence: 91%
“…The main types of morbidity reported were also similar with the majority experiencing near vision problems and gradual loss of vision. Similar to other studies, a higher prevalence of self-reported OM in Sri Lanka was associated with being a female and belonging to lower SES [1,4].…”
Section: Discussionsupporting
confidence: 88%
“…The high prevalence of self-reported OM in this study is not surprising as, in contrast to other studies of OM which included people of all ages [1,3,4], this survey focused on those aged 40 years, the majority of whom would have presbyopia. For example, in the Nigerian survey, which included all age groups, 84.6% of those aged 55 years reported ocular morbidity [4]. The main types of morbidity reported were also similar with the majority experiencing near vision problems and gradual loss of vision.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition to blinding eye conditions, many people in SSA suffer from non-blinding ocular conditions such as trauma, conjunctivitis, and presbyopia [ 3 , 4 ]. Although non-blinding and often self-limiting, these conditions can cause pain and irritation and potentially impede an individual’s ability to participate fully in society or economic activities.…”
Section: Introductionmentioning
confidence: 99%